Cold‐adapted influenza‐vectored RSV vaccine protects BALB/c mice and cotton rats from RSV challenge - Xu, Yongru; Sun, Fang; Bai, Zhifang; Bian, Chengrong; Wang, Xiliang; Zhao, Zhongpeng; Yang, Penghui (Journal of medical virology, 2024)
Respiratory syncytial virus (RSV) remains the primary cause of lower respiratory tract infections, particularly in infants and the elderly. In this study, we employed reverse genetics to generate a chimeric influenza virus expressing neuraminidase‐3F protein conjugate with three repeats of the RSV F protein protective epitope inserted into the NA gene of A/California/7/2009 ca (CA/AA ca), resulting in rFlu/RSV/NA‐3F (hereafter, rFRN3). The expression of NA‐3F protein was confirmed by Western blotting. The morphology and temperature‐sensitive phenotype of rFRN3 were similar to CA/AA ca. Its immunogenicity and protective efficiency were evaluated in BALB/c mice and cotton rats. Intranasal administration of rFRN3 elicited robust humoral, cellular, and to some extent, mucosal immune responses. Compared to controls, rFRN3 protected animals from RSV infection, attenuated lung injury, and reduced viral titers in the nose and lungs post‐RSV challenge. These results demonstrate that rFRN3 can trigger RSV‐specific immune responses and thus exhibits potent protective efficacy. The “dual vaccine” approach of a cold‐adapted influenza vector RSV vaccine will improve the prophylaxis of influenza and RSV infection. rFRN3 thus warrants further clinical investigations as a candidate RSV vaccine.